Grisotti flap reconstruction: on the edge of breast conserving surgery - Ormonde,Mariana (2020)
Overview and aims: Breast tumors that invade or are proximal to the nipple-areolar complex (NAC) have been classically treated with mastectomy. As an alternative, on the edge of breast conserving surgery, these cases may be approached using central lumpectomy and immediate reconstruction with Grisotti flap. The aim of this study was to determine the involved margins rate and locoregional and systemic relapse rates in patients that underwent this surgical technique. Study Design: Retrospective observational descriptive study. Population: Women that underwent central lumpectomy and Grisotti flap reconstruction in our center, during a 4-year period. Methods: We reviewed clinical charts on patients data including: diagnosis, indication for surgery, pathological findings, adjuvant treatments and relapse. Descriptive and bivariate analysis was performed. Results: A total of 45 women were enrolled in the study. From these, 82.2% had invasive breast cancer, and the others had in situ disease. For characterization of tumor proximity to NAC, all patients were evaluated using Magnetic Resonance Imaging. All women underwent central lumpectomy with NAC excision, followed by Grisotti flap reconstruction. From these, 68.9% also underwent contralateral symmetrization on the same operating time. Also, in 80% we were able to perform sentinel lymph node biopsy and in 20% axillary lymphadenectomy was done. Median surgery duration was 71 minutes and median in-hospital stays was 1 day. In two cases, positive margins were present and reintervention was necessary. Considering other cancer treatments, 8.9% underwent neoadjuvant chemotherapy, 48.9% adjuvant chemotherapy, 93.3% radiotherapy and 88.9% hormonal therapy. For a median follow-up time of 31 months, we report one case of locoregional relapse and one case of systemic relapse. Conclusions: Central lumpectomy combined with immediate Grisotti flap reconstruction is a good alternative for centrally located breast tumors. We report low positive margins rates (4.4%) and low relapse rates (2.3% for locoregional and 2.3% for systemic relapse).